2006
DOI: 10.1128/mcb.00597-06
|View full text |Cite
|
Sign up to set email alerts
|

AML1/RUNX1 Phosphorylation by Cyclin-Dependent Kinases Regulates the Degradation of AML1/RUNX1 by the Anaphase-Promoting Complex

Abstract: AML1 (RUNX1) regulates hematopoiesis, angiogenesis, muscle function, and neurogenesis. Previous studies have shown that phosphorylation of AML1, particularly at serines 276 and 303, affects its transcriptional activation. Here, we report that phosphorylation of AML1 serines 276 and 303 can be blocked in vivo by inhibitors of the cyclin-dependent kinases (CDKs) Cdk1 and Cdk2. Furthermore, these residues can be phosphorylated in vitro by purified Cdk1/cyclin B and Cdk2/cyclin A. Mutant AML1 protein which cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 47 publications
6
86
0
Order By: Relevance
“…1C, lanes 7 and 8). This result is consistent with studies that showed that the C termini of RUNX1 and RUNX2 harbor mitotic kinase CDK1 phosphorylation sites (13)(14)(15)(16).…”
Section: Significancesupporting
confidence: 82%
See 1 more Smart Citation
“…1C, lanes 7 and 8). This result is consistent with studies that showed that the C termini of RUNX1 and RUNX2 harbor mitotic kinase CDK1 phosphorylation sites (13)(14)(15)(16).…”
Section: Significancesupporting
confidence: 82%
“…CDK1-mediated phosphorylation of RUNX2 enhanced DNA binding activity, suggesting a role for RUNX2 in G 2 /M progression (15). In addition, CDK1/2 phosphorylates RUNX1, promoting its degradation by CDC20-associated anaphase-promoting complex during the late stages of mitosis (13,16). However, despite these findings, the significance of RUNX hyperphosphorylation in mitosis remains unclear.…”
mentioning
confidence: 69%
“…In a recent study, Ser 276 was reported to be also a target of Cdk1 and Cdk2 phosphorylation, which marks RUNX1 for Cdc20-dependent anaphase-promoting complex degradation. 49 Interestingly, in their system, the authors reported residual phosphorylation of RUNX1 persisted in the presence of multiple Cdk-specific inhibitors, suggesting that Ser 276 can serve concurrently as the target for several kinases. 49 In a related study, Aikawa et al recently reported the phosphorylation of RUNX1 and p300 by HIPK2 and HIPK1.…”
Section: Discussionmentioning
confidence: 99%
“…49 Interestingly, in their system, the authors reported residual phosphorylation of RUNX1 persisted in the presence of multiple Cdk-specific inhibitors, suggesting that Ser 276 can serve concurrently as the target for several kinases. 49 In a related study, Aikawa et al recently reported the phosphorylation of RUNX1 and p300 by HIPK2 and HIPK1. 28 Using a proteomic approach, they observed the phosphorylation of Ser 249 and Ser 276 in phosphorylated RUNX1 proteins isolated from myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation